2022
DOI: 10.1111/ppc.13043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sleep hygiene training given to elderly individuals on daytime sleepiness and fatigue: A randomized controlled trial

Abstract: Purpose This study was conducted to determine the effect of sleep hygiene training given to elderly individuals on daytime sleepiness and fatigue. Design and Methods The sample size was calculated by G. Power and determined as 134 elderly individuals. The experimental group was trained in sleep, two sessions a week for a total of 2 weeks. Findings The difference between Epworth Sleepiness Scale and Fatigue Severity Scale posttest mean scores of the elderly individuals in the experimental and control groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…Likewise, Borzou et al examined the effect of sleep hygiene education on the severity of fatigue and sleep quality of hemodialysis patients and found that sleep hygiene education can play a significant role in reducing the fatigue of hemodialysis patients (34). Similar findings were reported in the literature (43)(44)(45).…”
Section: Discussionsupporting
confidence: 52%
“…Likewise, Borzou et al examined the effect of sleep hygiene education on the severity of fatigue and sleep quality of hemodialysis patients and found that sleep hygiene education can play a significant role in reducing the fatigue of hemodialysis patients (34). Similar findings were reported in the literature (43)(44)(45).…”
Section: Discussionsupporting
confidence: 52%